COMPUTER NETWORKS VIRTUALIZATION COST EFFECTIVE AND DISTANCE LEARNING ACHIEVEMENT - KETI, FARIS (Journal of Duhok University, 2017)
In the curricula of higher education faculties, computer networking is a main topic in computer Science courses. Previous methods of teaching a subject like Computer Networks has consisted of a face to face proposal, high cost labs and static and complex configuration of real networking devices restricted by in location attendance for experiment purposes and in lab work. With computer networks virtualization, Students and researchers are allowed to do tests on real world networking configuration scenarios and to configure various and complex network scenarios by configuring virtualized equipments, such as routers and switches, through virtual consoles and Network virtualization and simulation tools . In this paper an evaluation of the concept of computer networks virtualization and Software Defined Networks is conducted which can be used by the students to improve the learning process of computer networks subject in engineering studies. Emulating the same physical networks as in the laboratory, at home or remotely from anywhere with more flexibility and lower cost, all that through emulation tools installed on students computers.